Complexeation Behavior of CoII, NiII, CuII, ZnII, and CdII Ions Toward Schiff Base Derived From 2, 4 -Dihydroxy Benzaldehyde and O-Phenylene Diamine - Numan, A. .T.; Sultan, K. .M.; Abdullah, A.S. (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2017)
The aim of this work covers the synthesis and characterization of the new tertra dentate ligand (H4L) containing (N and O) as donor set atoms kind (N2O2) where: H4L=Bis-1,2 (2,4dihydroxybenzylediene phylinediamine . The preparation of ligand contains reaction 2, 4 Dihydroxy benzaldehyde and o-phenylene diamine . Schiff base was reacted with some metal ions in the presence of methanol to give the complexes in the general formula [M (H2L)] where: MII = Co, Ni, Cu, Zn, Cd. All compounds were characterized by spectroscopic methods I.R , U.V.-Vis, metal content and molar conductivity measurements, showed that the complexes are non-electrolyte. The proposed geometry for all of the proposed complexes was a tetrahedral while Ni complex was square planar.